Green Organizational Culture: A Bibliometric Analysis - Lopes , Joana; Almeida , Juna; Rebelo , Teresa (Conferência - Investigação e Intervenção em Recursos Humanos, 2023)
The multiple attempts to solve environmental problems without particularly success seems to suggest that it is necessary to change behaviours and culture (Adams et al., 2018). It is known that the human factor is the main contribution to environmental problems (Intergovernmental Panel on Climate Change, 2021), which has led organizations to recognize their role as agents of change. It is in this context that it is important to consider green organizational culture. Organizational culture is a well-established construct and with the spread of environmental concerns, the definition presented by Schein was adapted and led to the definition of green organizational culture – “A pattern of shared basic assumptions learned by a group as it adapts to the challenges posed by human activity’s impact on the natural environment in a way that permits day-to-day functioning, which has worked well enough to be considered valid and, therefore, to be taught to new members as the correct way to perceive, think, and feel in relation to environmental sustainability” (Norton et al., 2015, pp. 329-330). Therefore, we conducted a research that aimed to map the topic, in order to acknowledge the evolution of the construct in the 2011 to 2022 time span. This assumes particular relevance both from a theoretical and practical point of view, as it enhances knowledge on the subject and generates inputs for organizational intervention. To this end, a bibliometric analysis was carried out, using a title, abstract and keyword search with the terms “environmental organizational culture”, “pro-environmental organizational culture”, “eco-friendly organizational culture” and “pro-environmental culture”, as these are the different terminologies used in the literature. The research was conducted in the Scopus database, which is recommended for carrying out bibliometric analysis for new smaller research fields (Zupic & Čater, 2015), like green organizational culture. Furthermore, the research began in 2011 because it was the first year with publications. From the analysis of the 54 results obtained, we can state that the number of publications has undergone a positive evolution. Since the beginning of the publications in the area, it has had a significant growth, namely from 2020, with the highest value in 2022 (twenty publications). This trend is equally true when we analyse the number of citations per year, in which there is a significant positive evolution, especially since 2018, where the number of citations has steadily increased, reaching its peak in 2022, with 455 citations. Regarding the authorship of the publications, there are 151 authors, and the author who most published in the period under analysis was N. T. Pham, accounting a total of four publications. He is followed by the authors Y. S. Chen and Z. Tučková, with three publications each. It should also be noted that the publications are spread over 40 journals. Three journals stand out for having published three articles during the period analysed: International Journal of Sustainable Development and Planning, Journal of Cleaner Production, and Sustainability Switzerland. The results obtained indicate the top-5 most cited publications, that belong, from the most cited to the less cited authors, to Chen (169), Gürlek & Tuna (122), Duarte & Cruz- Machado (117), Evangelista et al. (68) and Chang (65 citations). Four of which are empirical and the remaining one is a review article (Duarte & Cruz-Machado, 2013). The analysis of the five articles allows us to conclude the importance of green organizational culture, as a source for organizations to obtain competitive advantage and to assume themselves as agents of change in environmental matters (Duarte & Cruz- Machado, 2013). Moreover, it shows that green organizational culture is related with other variables, like green leadership, green organizational identity (Chen, 2011), green innovation (Gürlek & Tuna, 2017), organizational support, employee’s involvement (Evangelista et al., 2017) and proactive corporate social responsibility (Chang, 2015). In short, green organizational culture is a growing construct, and studies point to the importance of developing and promoting scientific knowledge in this area, in order to contribute to environmental sustainability through organizations as agents of change.